The Effect of Hormonal Composition, Type of Explant and Light Condition on Callus Production in Periwinkle (Catharanthus roseus L.) (Plant Tissue Culture and Biotechnology, 2013)
Plant Tissue Cult. & Biotech. 23(1): 107?113, 2013 (June)DOI: http://dx.doi.org/10.3329/ptcb.v23i1.15567